Testosterone Therapy Could Be a Potential Approach For Treatment of Elderly Male COVID-19 Patients- A Review (Journal of Bio-Science, 2021)
The emerging SARS-CoV-2 (2019-nCoV) is still following the increasing trend of infection worldwide with an elderly male predominance. Studies reported that majority of male patients with COVID-19 suffer from severe testosterone deficiency and are likely to die from the coronavirus mainly due to a less effective immune response and high level of pro-inflammatory cytokines, a condition called cytokine storm. Testosterone (a steroid having protective anti-inflammatory properties) therapy reduces circulating levels of pro-inflammatory cytokines. Testosterone therapy is effective in the management of elderly Alzheimer's disease where pro-inflammatory cytokines are the potent mediators of inflammatory processes, and aged men having HIV infection. As, currently there is no specific therapeutic drug targeting the SARS-CoV-2, and, considering the present pandemic circumstance, and the immunomodulatory and protective findings of testosterone therapy in previous studies, it can be hypothesized that testosterone therapy could be a potential approach for treatment of elderly male COVID-19 patients.J. Bio-Sci. 29(1): 181-187, 2021 (June)